2007
DOI: 10.1021/jp0656429
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Al-Doped Boron Clusters by the Density-Functional Theory

Abstract: The geometries, stabilities, and electronic properties of Bn and AlBn clusters, up to n=12, have been systematically investigated by using the density-functional approach. The results of Bn clusters are in good agreement with previous conclusions. When the Al atom is doped in Bn clusters, the lowest-energy structures of the AlBn clusters favor two-dimensional and can be obtained by adding one Al atom on the peripheral site of the stable Bn when n Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
78
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 26 publications
19
78
3
Order By: Relevance
“…[14] On the other hand, extensive experimental and theoretical studies on carbon-boron mixed clusters have been carried out [15][16][17] since a prediction on the existence of planar hexa-coordinated carbon in B 6 C 2À clusters. [15] Boron-silicon compounds have attracted considerable interest due to their potentially important applications in the fields of semiconductor materials and thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] On the other hand, extensive experimental and theoretical studies on carbon-boron mixed clusters have been carried out [15][16][17] since a prediction on the existence of planar hexa-coordinated carbon in B 6 C 2À clusters. [15] Boron-silicon compounds have attracted considerable interest due to their potentially important applications in the fields of semiconductor materials and thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…A study of phase diagrams of the boron-silicon binary systems indicated the existence of two kinds of B n Si compounds in the boron-rich region (n = 16-26 and also B 6 Si). [18] The B 14 Si cluster was synthesized for the first time by Giese et al, [19] and Imai et al presented X-ray images and studies of the electronic properties of singlet crystal B 18 Si. [20] However, in spite of the demonstrated importance of the boron-silicon compounds, the understanding of the electronic and thermodynamic properties of these materials is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2d shows variation of average Al-Al distance of the most stable clusters as a function of cluster size. As can be seen in this figure the average Al-Al distance gradually increases with cluster size while having local oscillation at Al 5 , Al 8 and Al 12 and finally approaches the bulk limit of 2.86 Å [2]. It seems that, unlike binding energy per atom, the average Al-Al distance of the most stable Al n clusters approaches the bulk value rather rapidly with cluster size.…”
Section: Resultsmentioning
confidence: 68%
“…G* level of theory energy (E f ) which were calculated according to the Eqs. 2 and 3, respectively [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation